Металлические наконечники стрел Переднего Востока и евразийских степей II - первой половины I тысячелетия до н.э. - Медведская, И. H.
Medvedskaja, I. N.; Metal Arrowheads of the IInd-First Half of the 1st Mill. B.C. from the Near East and the Eurasian Steppes; engl. Résumé.